Acquired factor XI inhibitor in chronic lymphocytic leukaemia. Issue 4 (April 1992) - Goodrick, M J; Prentice, A G; Copplestone, J A; Pamphilon, D H; Boon, R J
Abstract : A 71 year old man with chronic lymphocytic leukaemia (CLL) experienced excessive bleeding following transurethral resection of the prostate. Investigations showed a prolonged kaolin cephalin clotting time (KCCT) with low concentrations of factor XI. The prolonged KCCT was largely corrected by mixing with normal plasma but this correction was lost on incubation, confirming the presence of an inhibitor. He was treated with pulsed methylprednisolone and chlorambucil which resulted in the resolution of the bleeding problem and the loss of detectable circulating inhibitor.